Hubungan Antara Kecerdasan Emosional dan Academic Burnout dengan Prestasi Belajar Siswa SMPN 2 Pakis Kabupaten Malang - Aulia Widya Kirana; Elia Flurentin; Arbin Janu Setiyowati; Aulia Widya Kirana; Elia Flurentin (Universitas Negeri Malang, 2023)
Abstract: The purpose of this study was to determine the relationship between emotional intelligence and academic burnout with learning achievement. This study used correlational research design. The total population of class VIII students of SMP Negeri 2 Pakis is 156 students, the sample is 112 students obtained by the slovin formula with a 5 percent allowance. Sampling using simple random sampling method. Data collection used the emotional intelligence scale adapted by Bantolo (2020), and the academic burnout scale